Anti-diabetic effects of Dachaihu decoction combined with Sanghuangporus vaninii: insights from network pharmacology, intestinal flora, and liver metabolomics - Huang, Juntao; Lin, Yanfa; Huang, Zifeng; Li, Tiantian; Ge, Xiaodong; Liu, Bin; Huang, Zirui (Frontiers in Cell and Developmental Biology, 2025)
Numerous studies have demonstrated the therapeutic effects of the traditional Chinese medicinal fungus Sanghuangporus vaninii on type 2 diabetes mellitus (T2DM), yet the underlying mechanisms remain unclear. This study aimed to investigate the anti-diabetic and hypolipidemic effects of the S. vaninii combined with Dachaihu decoction formulation (DCHD-SV) in T2DM mice and deeply explore its action mechanisms through network pharmacology, 16S RNA sequencing, and liver metabolomics. The results showed that DCHD-SV can effectively ameliorate relevant symptoms of T2DM in mice, including hyperglycemia, dyslipidemia, insulin resistance, and organ damage. In addition, DCHD-SV modulates the intestinal flora and liver metabolites of T2DM mice, and may exert its anti-diabetic effects through the PPARγ/AMPK/mTOR signaling pathway. These findings underscore DCHD-SV as a promising candidate for T2DM therapy and lay a theoretical foundation for further investigating its mechanisms.